Inventarisasi Cerita Rakyat Nyi Ageng Bakaran Desa Juwana Kabupaten Pati (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
Protection of oral literature from extinction can be done by an inventory program in the form of transferring texts from oral tradition to written literature. The folklore (legend) of Nyai Ageng Bakaran folklore originates from a village in the Juwana District, Pati Regency, Central Java. This story underlies traditions still carried out by the people of Bakaran Wetan village. This study aims to describe the structure and function of the legend of Nyai Ageng Bakaran. The oral literary tradition will recede with the reduction of actors and supporters of literary activities in society. Folklore inventory is an effort to document oral literature in the context of conservation and protection of folklore sources so that they can be maintained for the future. Data collection techniques use interview techniques and literature studies. Data analysis was carried out by collecting information with triangulation techniques from 3 speakers, voice recordings, and narrative texts in the form of notes from research results and data analysis techniques with the theory of structure and folkloric functions. The results of the research on the structure and function of the legend of Nyai Ageng Bakaran are intrinsic elements in the form of plots that contain the narrative units of this story, characters and characterizations, and the story's setting. Then, the function of legend is in the form of a description of 4 folkloric processes taken from William Bascom's theory, namely function as a projection system, as a tool for attestation of institutions and cultural institutions, as a child education tool (pedagogical device), as a tool of coercion and supervision so that its collective members will always obey the norms of society. Keywords: folklore; folklore Structure; folklore function; legend